Practical adaptive fuzzy H∞ tracking control of uncertain nonlinear systems - Pan, Yongping (2015)
This paper presents a practical direct adaptive fuzzy H∞ tracking control (AFHC) approach for a class of uncertain nonlinear systems with unknown control gain functions and external disturbances. A modified output tracking error is defined to eliminate high gain at the control input and to improve transient performance. An ideal control law is developed to eliminate the restriction that the control gain function must be known a priori under the direct adaptive scheme. A nonlinearly parameterized fuzzy system without redundant parameters is proposed to online approximate the ideal control law. The direct AFHC is derived by virtue of the Lyapunov synthesis, where both the antecedent and the consequent parameters of fuzzy rules are updated by the proposed adaptive law. Simulation studies have demonstrated that the proposed approach can outperform previous approaches with similar or less control efforts.